2007
DOI: 10.1021/ie070297a
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Physical Changes in Phenol−Formaldehyde Resol Resin, as a Function of the Degree of Condensation of the Resol Solution

Abstract: The structural and physical differences of phenol-formaldehyde resol resins collected during a resin synthesis were studied, as a function of the degree of condensation of the resin. The structural and physical properties of the resins were analyzed using nuclear magnetic resonance (NMR) spectroscopy, viscosity and refractive index measurements, gel permeation chromatography (GPC), differential scanning calorimetry (DSC), solids content analyses, and contact angle determinations on wood veneer. As a result of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 43 publications
4
22
0
1
Order By: Relevance
“…The wettability of wood samples reduced with the increased viscosity of adhesives, consistent with the literature (Gavrilovic-Grmusa et al 2012;Monni et al 2007). Furthermore, the changes in surface tension of the three adhesives were not significant (from 66.87 mJ/m 2 to 68.23 mJ/m 2 , as shown in Table 1); therefore, the differences in contact angle were caused mainly by the change in viscosity.…”
Section: Dynamic Wettabilitysupporting
confidence: 87%
See 1 more Smart Citation
“…The wettability of wood samples reduced with the increased viscosity of adhesives, consistent with the literature (Gavrilovic-Grmusa et al 2012;Monni et al 2007). Furthermore, the changes in surface tension of the three adhesives were not significant (from 66.87 mJ/m 2 to 68.23 mJ/m 2 , as shown in Table 1); therefore, the differences in contact angle were caused mainly by the change in viscosity.…”
Section: Dynamic Wettabilitysupporting
confidence: 87%
“…The frictional heat generated by rotary machining can be expected to cause these materials to migrate to the surface and smear over the surface of the wood, and a hydrophobic wood surface can be caused. The tight side and loose side also had different behaviors of wettability (Vázquez et al 2003) because the wood surface was more dense on the tight side than on the loose side (Monni et al 2007). As is shown in Table 1, the standard deviations of the contact angles were small; therefore, it could be concluded that the calculation method for acquiring the contact angle values is suitable.…”
Section: Contact Anglementioning
confidence: 98%
“…1 It is widely accepted that formaldehyde emissions from panels used in interior applications is a leading cause of sick building syndrome (SBS) in indoor environments. 2 However, formaldehyde emissions from PF resinbonded wood products are very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Di samping itu perekat UF dan air destilasi pada suhu yang sama memiliki viskositas sebesar 1,2 dan 0,008 poise. Keterbasahan permukaan bahan menurun seiring tingginya nilai viskositas cairan (Monni, et al, 2007;Gavrilovic-Grmusa, et al, 2012a, 2012bGavrilovic-Grmusa, et al, 2013). Berikutnya faktor lain yang berpengaruh terhadap proses pembasahan sangat kompleks, di antaranya adalah pH permukaan seperti yang dijelaskan oleh Gérardin, et al (2007).…”
Section: Keterbasahan Dinamis (Dynamic Wettability)unclassified